The Borzoi practice book for writers - Hennessy, Michael
The Borzoi Practice Book for Writers, third edition, is a collection of some 240 exercises designed to accompany The Borzoi Handbook for Writers, third edition. While offering a full range of exercises for students who need individual instruction, the Practice Book also includes ample material for group work and class discussion. And since it comes free, shrink-wrapped with every new copy of the Handbook, instructors can draw on its many resources without adding cost for their students.